Polskie kolejowe porozumienia graniczne w okresie PRL na wybranych przykładach - Keller, Dawid (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2022)
Among the issues that researchers have almost never analyzed is the railway cross-border traffic in the period of 1945–1989. The article presents the legal and organizational context of the relations between Polish, Czechoslovak and Soviet state railway entities in southeast Poland, outlines the related difficulties and international background, and reconstructs the course of crucial investments within the borderland, such as rebuilding of the Łupków border crossing.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne